Rezension zu: Bernardo Bátiz-Lazo: Cash and Dash. How ATMs and Computers Changed Banking - Schmitt, Martin (Vierteljahrschrift für Sozial- und Wirtschaftsgeschichte)
Keywords: Wirtschaftsgeschichte; Bankengeschichte; Geldautomat; ATM; Geschichte; Technikgeschichte

Unconventional phase III of high-pressure solid hydrogen - Azadi, Sam; Kühne, Thomas D. (Physical Review B)

Random network models with variable disorder of geometry - Klümper, A.; Nuding, W.; Sedrakyan, A. (Physical Review B)

Narratives of Vicarious Experience in Oral History Interviews with Craft Artists - Mildorf, Jarmila (Journal of Pragmatics)

Spatially asymmetric transients of propagating exciton-polariton modes in a planar CdZnTe/CdMgTe guiding structure - Vondran, J.; Spitzer, F.; Bayer, M.; Akimov, I. A.; Trautmann, Alexander; Reichelt, Matthias; Meier, Cedrik; Weber, N.; Meier, Torsten; André, R.; Mariette, H. (Physical Review B)

Excited-state band mapping and momentum-resolved ultrafast population dynamics in In/Si(111) nanowires investigated with XUV-based time- and angle-resolved photoemission spectroscopy - Nicholson, C. W.; Puppin, M.; Lücke, A.; Gerstmann, Uwe; Krenz, Marvin; Schmidt, Wolf Gero; Rettig, L.; Ernstorfer, R.; Wolf, M. (Physical Review B)

Higher-order contributions and nonperturbative effects in the nondegenerate nonlinear optical absorption of semiconductors using a two-band model - Hannes, Wolf-Rüdiger; Meier, Torsten (Physical Review B)

Spatially asymmetric transients of propagating exciton-polariton modes in a planar CdZnTe/CdMgTe guiding structure - Vondran, J.; Spitzer, F.; Bayer, M.; Akimov, I. A.; Trautmann, Alexander; Reichelt, Matthias; Meier, Cedrik; Weber, N.; Meier, Torsten; André, R.; Mariette, H. (Physical Review B)

Ballistic photocurrents in semiconductor quantum wells caused by the excitation of asymmetric excitons - Duc, Huynh Thanh; Ngo, Cong; Meier, Torsten (Physical Review B)

Decay and revival of electron spin polarization in an ensemble of (In,Ga)As quantum dots - Evers, E.; Belykh, V. V.; Kopteva, N. E.; Yugova, I. A.; Greilich, A.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review B)

Spin inertia of resident and photoexcited carriers in singly charged quantum dots - Zhukov, E. A.; Kirstein, E.; Smirnov, D. S.; Yakovlev, D. R.; Glazov, M. M.; Reuter, Dirk; Wieck, A. D.; Bayer, M.; Greilich, A. (Physical Review B)

Theory of spin inertia in singly charged quantum dots - Smirnov, D. S.; Zhukov, E. A.; Kirstein, E.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M.; Greilich, A.; Glazov, M. M. (Physical Review B)

Probing quasi-one-dimensional band structures by plasmon spectroscopy - Lichtenstein, T.; Mamiyev, Z.; Braun, C.; Sanna, S.; Schmidt, Wolf Gero; Tegenkamp, C.; Pfnür, H. (Physical Review B)

Calculation of spin-spin zero-field splitting within periodic boundary conditions: Towards all-electron accuracy - Biktagirov, Timur; Schmidt, Wolf Gero; Gerstmann, Uwe (Physical Review B)

Vibrational properties of the Au-(3×3)/Si(111) surface reconstruction - Halbig, B.; Liebhaber, M.; Bass, U.; Geurts, J.; Speiser, E.; Räthel, J.; Chandola, S.; Esser, N.; Krenz, Marvin; Neufeld, Sergej; Schmidt, Wolf Gero; Sanna, S. (Physical Review B)

Probing quasi-one-dimensional band structures by plasmon spectroscopy - Lichtenstein, T.; Mamiyev, Z.; Braun, Christian; Sanna, S.; Schmidt, Wolf Gero; Tegenkamp, C.; Pfnür, H. (Physical Review B)

Microscopic theory of cavity-enhanced single-photon emission from optical two-photon Raman processes - Breddermann, Dominik; Praschan, Tom; Heinze, Dirk Florian; Binder, Rolf; Schumacher, Stefan (Physical Review B)

Polytypism driven zero-field splitting of silicon vacancies in 6H-SiC - Biktagirov, Timur; Schmidt, Wolf Gero; Gerstmann, Uwe; Yavkin, Boris; Orlinskii, Sergei; Baranov, Pavel; Dyakonov, Vladimir; Soltamov, Victor (Physical Review B)

Spin pairing versus spin chains at Si(553)-Au surfaces - Braun, Christian; Gerstmann, Uwe; Schmidt, Wolf Gero (Physical Review B)

Metal-insulator transition in the dimerized organic conductor κ−(BEDT-TTF)2Hg(SCN)2Br - Ivek, Tomislav; Beyer, Rebecca; Badalov, Sabuhi; Čulo, Matija; Tomić, Silvia; Schlueter, John A.; Zhilyaeva, Elena I.; Lyubovskaya, Rimma N.; Dressel, Martin (Physical Review B)

Spin dynamics of quadrupole nuclei in InGaAs quantum dots - Kuznetsova, M. S.; Cherbunin, R. V.; Gerlovin, I. Ya.; Ignatiev, I. V.; Verbin, S. Yu.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review B)

Photon echoes from (In,Ga)As quantum dots embedded in a Tamm-plasmon microcavity - Salewski, M.; Poltavtsev, S. V.; Kapitonov, Yu. V.; Vondran, J.; Yakovlev, D. R.; Schneider, C.; Kamp, M.; Höfling, S.; Oulton, R.; Akimov, I. A.; Kavokin, A. V.; Bayer, M. (Physical Review B)
We report on the coherent optical response from an ensemble of (In,Ga)As quantum dots (QDs) embedded in a planar Tamm-plasmon microcavity with a quality factor of approximately 100. Significant enhancement of the light-matter interaction is demonstrated under selective laser excitation of those quantum dots which are in resonance with the cavity mode. The enhancement is manifested through Rabi oscillations of the photon echo, demonstrating coherent control of excitons with picosecond pulses at intensity levels more than an order of magnitude smaller as compared with bare quantum dots. The decay of the photon echo transients is weakly changed by the resonator, indicating a small decrease of the coherence time T2 which we attribute to the interaction with the electron plasma in the metal layer located close (40 nm) to the QD layer. Simultaneously we see a reduction of the population lifetime T1, inferred from the stimulated photon echo, due to an enhancement of the spontaneous emission by a factor of 2, which is attributed to the Purcell effect, while nonradiative processes are negligible, as confirmed from time-resolved photoluminescence.

Double resonant plasmonic nanoantennas for efficient second harmonic generation in zinc oxide - Weber, Nils; Protte, Maximilian; Walter, Felicitas; Georgi, Philip; Zentgraf, Thomas; Meier, Cedrik (Physical Review B)

Solving the Bethe-Salpeter equation for the second-harmonic generation in Zn chalcogenides - Riefer, A.; Schmidt, Wolf Gero (Physical Review B)

Understanding band alignments in semiconductor heterostructures: Composition dependence and type-I–type-II transition of natural band offsets in nonpolar zinc-blendeAlxGa1−xN/AlyGa1−yNcomposites - Landmann, M.; Rauls, E.; Schmidt, Wolf Gero (Physical Review B)

Electron paramagnetic resonance calculations for hydrogenated Si surfaces - Rohrmüller, M.; Schmidt, Wolf Gero; Gerstmann, Uwe (Physical Review B)

Tuning the conductivity along atomic chains by selective chemisorption - Edler, F.; Miccoli, I.; Stöckmann, J. P.; Pfnür, H.; Braun, Christian; Neufeld, Sergej; Sanna, S.; Schmidt, Wolf Gero; Tegenkamp, C. (Physical Review B)

Understanding band alignments in semiconductor heterostructures: Composition dependence and type-I–type-II transition of natural band offsets in nonpolar zinc-blendeAlxGa1−xN/AlyGa1−yNcomposites - Landmann, M.; Rauls, E.; Schmidt, Wolf Gero (Physical Review B)

Vortex-vortex control in exciton-polariton condensates - Ma, Xuekai; Schumacher, Stefan (Physical Review B)

Anisotropic excitons and their contributions to shift current transients in bulk GaAs - Podzimski, Reinold; Duc, Huynh Thanh; Meier, Torsten (Physical Review B)

Time-resolved photon echoes from donor-bound excitons in ZnO epitaxial layers - Poltavtsev, S. V.; Kosarev, A. N.; Akimov, I. A.; Yakovlev, D. R.; Sadofev, S.; Puls, J.; Hoffmann, S. P.; Albert, M.; Meier, Cedrik; Meier, Torsten; Bayer, M. (Physical Review B)

Damping of Rabi oscillations in intensity-dependent photon echoes from exciton complexes in a CdTe/(Cd,Mg)Te single quantum well - Poltavtsev, S. V.; Reichelt, Matthias; Akimov, I. A.; Karczewski, G.; Wiater, M.; Wojtowicz, T.; Yakovlev, D. R.; Meier, Torsten; Bayer, M. (Physical Review B)

Zwischen Wissenschaft und Lebenswelt. Entwicklung, Stand und Zukunftsperspektiven haushaltsbezogener Bildung. - Schlegel-Matthies, Kirsten

All-optical tailoring of single-photon spectra in a quantum-dot microcavity system - Breddermann, D.; Heinze, Dirk Florian; Binder, R.; Zrenner, Artur; Schumacher, Stefan (Physical Review B)

Electron spin dynamics in cubic GaN - Buß, J. H.; Schupp, T.; As, Donat Josef; Brandt, O.; Hägele, D.; Rudolph, J. (Physical Review B)

Stabilizing nuclear spins around semiconductor electrons via the interplay of optical coherent population trapping and dynamic nuclear polarization - Onur, A. R.; de Jong, J. P.; O'Shea, D.; Reuter, Dirk; Wieck, A. D.; van der Wal, C. H. (Physical Review B)

Reconstruction of nuclear quadrupole interaction in (In,Ga)As/GaAs quantum dots observed by transmission electron microscopy - Sokolov, P. S.; Petrov, M. Yu.; Mehrtens, T.; Müller-Caspary, K.; Rosenauer, A.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

All-optical tailoring of single-photon spectra in a quantum-dot microcavity system - Breddermann, D.; Heinze, D.; Binder, R.; Zrenner, Artur; Schumacher, Stefan (Physical Review B)
Semiconductor quantum-dot cavity systems are promising sources for solid-state-based on-demand generation of single photons for quantum communication. Commonly, the spectral characteristics of the emitted single photon are fixed by system properties such as electronic transition energies and spectral properties of the cavity. In the present work we study cavity-enhanced single-photon generation from the quantum-dot biexciton through a partly stimulated nondegenerate two-photon emission. We show that frequency and linewidth of the single photon can be fully controlled by the stimulating laser pulse, ultimately allowing for efficient all-optical spectral shaping of the single photon.

Existence of topological nontrivial surface states in strained transition metals: W, Ta, Mo, and Nb - Thonig, Danny; Rauch, Tomáš; Mirhosseini, Hossein; Henk, Jürgen; Mertig, Ingrid; Wortelen, Henry; Engelkamp, Bernd; Schmidt, Anke B.; Donath, Markus (Physical Review B)

Orbital-symmetry-selective spin characterization of Dirac-cone-like state on W(110) - Miyamoto, K.; Wortelen, H.; Mirhosseini, Hossein; Okuda, T.; Kimura, A.; Iwasawa, H.; Shimada, K.; Henk, J.; Donath, M. (Physical Review B)

Experimental realization of a polariton beam amplifier - Niemietz, Dominik; Schmutzler, Johannes; Lewandowski, Przemyslaw; Winkler, Karol; Aßmann, Marc; Schumacher, Stefan; Brodbeck, Sebastian; Kamp, Martin; Schneider, Christian; Höfling, Sven; Bayer, Manfred (Physical Review B)

Dynamics of exciton-polaritons in discrete lattices under incoherent localized pumping - Yulin, A. V.; Chestnov, I. Yu.; Ma, X.; Schumacher, Stefan; Peschel, U.; Egorov, O. A. (Physical Review B)

Polarization dependence of nonlinear wave mixing of spinor polaritons in semiconductor microcavities - Lewandowski, Przemyslaw; Lafont, Ombline; Baudin, Emmanuel; Chan, Chris K. P.; Leung, P. T.; Luk, Samuel M. H.; Galopin, Elisabeth; Lemaître, Aristide; Bloch, Jacqueline; Tignon, Jerome; Roussignol, Philippe; Kwong, N. H.; et al. (Physical Review B)

Vibration eigenmodes of the Au-(5×2)/Si(111) surface studied by Raman spectroscopy and first-principles calculations - Liebhaber, M.; Halbig, B.; Bass, U.; Geurts, J.; Neufeld, Sergej; Sanna, S.; Schmidt, Wolf Gero; Speiser, E.; Räthel, J.; Chandola, S.; Esser, N. (Physical Review B)

LiNbO3 electronic structure: Many-body interactions, spin-orbit coupling, and thermal effects - Riefer, Arthur; Friedrich, Michael; Sanna, Simone; Gerstmann, Uwe; Schindlmayr, Arno; Schmidt, Wolf Gero (Physical Review B)
The influence of electronic many-body interactions, spin-orbit coupling, and thermal lattice vibrations on the electronic structure of lithium niobate is calculated from first principles. Self-energy calculations in the GW approximation show that the inclusion of self-consistency in the Green function G and the screened Coulomb potential W opens the band gap far stronger than found in previous G0W0 calculations but slightly overestimates its actual value due to the neglect of excitonic effects in W. A realistic frozen-lattice band gap of about 5.9 eV is obtained by combining hybrid density functional theory with the QSGW0 scheme. The renormalization of the band gap due to electron-phonon coupling, derived here using molecular dynamics as well as density functional perturbation theory, reduces this value by about 0.5 eV at room temperature. Spin-orbit coupling does not noticeably modify the fundamental gap but gives rise to a Rashba-like spin texture in the conduction band.

Strain-induced quasi-one-dimensional rare-earth silicide structures on Si(111) - Timmer, F.; Oelke, R.; Dues, C.; Sanna, S.; Schmidt, Wolf Gero; Franz, M.; Appelfeller, S.; Dähne, M.; Wollschläger, J. (Physical Review B)

Surface vibrational Raman modes of In:Si(111)(4×1)and(8×2)nanowires - Speiser, E.; Esser, N.; Wippermann, S.; Schmidt, Wolf Gero (Physical Review B)

Grand canonical Peierls transition in In/Si(111) - Jeckelmann, Eric; Sanna, Simone; Schmidt, Wolf Gero; Speiser, Eugen; Esser, Norbert (Physical Review B)

Rare-earth silicide thin films on the Si(111) surface - Sanna, S.; Dues, C.; Schmidt, Wolf Gero; Timmer, F.; Wollschläger, J.; Franz, M.; Appelfeller, S.; Dähne, M. (Physical Review B)

Atomic size effects studied by transport in single silicide nanowires - Miccoli, I.; Edler, F.; Pfnür, H.; Appelfeller, S.; Dähne, M.; Holtgrewe, K.; Sanna, S.; Schmidt, Wolf Gero; Tegenkamp, C. (Physical Review B)